ANALISIS KOMPARASI SEBARAN PADANG LAMUN MENGGUNAKAN METODE LYZENGA DI PANTAI UJUNG GENTENG SUKABUMI - Putri Okta Rinda; Fernandi Rahma Putri; Meliza Cahya Putri (Universitas Negeri Padang, 2023)
ecologically, and economically. Currently, the area of ​​seagrass beds continues to decrease. This is due to the lack of public knowledge regarding the role of seagrass ecosystems. For this reason, research was carried out so that this data could become knowledge related to the extent of seagrass distribution from several periods, namely 2015, 2018, and 2022. This research was carried out using the lyzenga method by utilizing remote sensing technology. The results of the classification will obtain two classes, namely seagrass and non-seagrass. In 2015 the seagrass area was 0.232548 km2 and the non-seagrass area was 9.823787 km2, in 2018 the seagrass area was 0.074101 km2 and the non-seagrass area was 6.918944 km2. Then, in 2022 the area of ​​seagrass beds will be 0.400978 km2 and non-seagrass areas will be 10.983756 km2. Between 2015 and 2018 there was a change in the area of ​​seagrass to a non-seagrass area of ​​0.158447 km2 and between 2018 and 2022 there was an increase in the area of ​​seagrass area of ​​0.326877 km2. Keywords: A seagrass ecosystem, Lyzenga, remote sensing